Comparison of Military Potentials of USA, PRC, and Some Countries in APR from the Standpoint of Western Analysts - M. Tchaikovsky; A. Kazantsev (Vestnik MGIMO-Universiteta)
The article gives a brief review of military and political situation in the Asian-Pasific Region against a background of its high-dynamic economic development. In connection with the rising significance of the APR in the global economy, Western military and political analysts consider the PRC power strengthening as a challenge to the security and impact of the USA not only in this region, but also globally. By their opinion, escalation of American- Chinese military opposition in the region leads to formation of new international polytical configuration in the filed of security and rising of new cold war mainly aimed at the APR. The dynamics of military expenditures of the key regional players is analyzed evidencing the fast grow of their military potentials. The article concludes that detailed analysis and study of scenarios of probable development of the situation in respect to effective securing of Russia's interests in the APR are necessary and important.